Innovative electrochemical electrode modified with Al2O3 nanoparticle decorated MWCNTs for ultra-trace determination of tamsulosin and solifenacin in human plasma and urine samples and their pharmaceutical dosage form. Issue 27 (13th June 2022) - Attia, Khalid A. M.; Abdel-Raoof, Ahmed M.; Serag, Ahmed; Eid, Sherif M.; Abbas, Ahmed E.
Abstract : A SWV method using a carbon paste electrode modified with aluminum oxide nanoparticle-decorated multi-walled carbon nanoparticles is presented for ultra-sensitive determination of tamsulosin and solifenacin, one of the most prescribed pharmaceutical combinations in urology. Abstract : A simple, cheap, sensitive, and time-saving square wave voltammetric (SWV) procedure using a carbon paste electrode modified with aluminum oxide nanoparticle decorated multi-walled carbon nanoparticles (Al2 O3 -NPs/MWCNTs/CPE) is presented for the ultra-sensitive determination of tamsulosin (TAM) and solifenacin (SOL), one of the most prescribed pharmaceutical combinations in urology. Characterization of the developed electrode was performed using scanning electron microscopy (SEM), X-ray diffraction (XRD) patterns, energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM) and FT-IR spectrophotometry. The voltammetric behavior of TAM/SOL was evaluated using Al2 O3 -NPs in different content and electrode compositions. The use of Al2 O3 functionalized MWCNTs as a CPE modifier increased the process of electron transfer as well as improved the electrode active surface area therefore, ultra-sensitive results were acquired with a linear range of 10–100 and 12–125 ng ml −1 for TAM and SOL respectively, and a limit of the detection value of 2.69 and 3.25 ng ml −1 for TAM and SOL, respectively. Interestingly, the proposed method succeeded in quantifying TAM and SOL with acceptable percentage recoveries in dosage forms having diverged concentration ranges and in the biological fluids with very low peak plasma concentration ( C max ). Furthermore, the proposed method was validated, according to the ICH criteria, and shown to be accurate and reproducible.